KEBIASAAN MENCATAT TRANSAKSI KEUANGAN DAN PENGARUH TINGKAT PENGHASILAN PADA KELUARGA AKUNTAN - Danyswara Madyasta (BAJ: Behavioral Accounting Journal, 2019)
Research Objectives to evaluate the habits of household accountants in recording family finances, because basically they have skills in terms of financial recording and reporting. This study uses a qualitative approach with several family accountant informants, both those who have habits and those who do not keep records of family finances. The results showed that family accountants who were not accustomed to recording family finances, often had many sudden and urgent family needs. They assume without doing the recording and analysis of perceived family financial budget more effectively, while the family accountant who initially make a habit of financial records of the family are accustomed to anymore because there is an increase in family income.